2020
DOI: 10.31436/imjm.v19i1.1327
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity among Primary Healthcare Workers In Perak, Malaysia

Abstract: Introduction: Overweight and obesity has been emerging as one of the most common and preventable nutritional problems worldwide. In 2016, 39% and 13% of the adult population worldwide was classified as overweight and obese, respectively. Materials and Methods: We conducted a cross-sectional study at 12 selected health clinics in Perak, Malaysia, and we used multi-stage cluster random sampling to determine the prevalence of overweight and obesity among the primary healthcare workers and the associate fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Overall, the prevalence of overweight and obesity among participants was high, with 43.8% categorised in this group. Local studies conducted regionally also reflected a similar trend, with a reported range of 29–49% prevalence of overweight and obese among healthcare workers [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 61%
“…Overall, the prevalence of overweight and obesity among participants was high, with 43.8% categorised in this group. Local studies conducted regionally also reflected a similar trend, with a reported range of 29–49% prevalence of overweight and obese among healthcare workers [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 61%
“…The study of Kasu et al 36 conducted in Ghana also found that more health workers were overweight (25.3%) than obese (12.7%). In contrast, health workers in a study in Malaysia 37 had a lower prevalence of abnormal BMIs (49.9%) with 28.4% being overweight and 21.5% obesity. The results of the current study cannot be ignored because of the effect of obesity on the productivity of health workers as well as the critical shortage of health workers.…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of obesity among HCWs is significantly higher than that among the Kelantan general population at 60%, based on data from the National Health and Morbidity Survey 2019, and the Malaysian general population, which was at 50.1% [16]. Another study conducted in Perak among HCWs found that 49.9% of HCWs were overweight or obese, similar to the national prevalence [17]. According to Avila et al (2015), obesity not only is linked to physical health outcomes but also has been extensively associated with mental illness [18].…”
Section: Discussionmentioning
confidence: 76%